Representation of non-communicable diseases in the Malaysian national strategic plan and medical brochures: a discourse-historical approach - Ling, Khai Lee; Kumaran Rajandran, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Non-communicable diseases (NCDs), such as heart disease and diabetes have a high mortality rate, which inspired governments to develop plans to manage NCDs. The Malaysian government produced the National Strategic Plan for Non-Communicable Diseases 2016-2025 (NSPNCD 2016-2025) and various brochures to enhance NCD prevention and management, and to inform the public about heart disease and diabetes. However, healthcare is one of the most prevalent contexts where stigmatization occurs. Unequal power relations in health discourse exists where language tends to tacitly blame chronic disease patients for poor health conditions. Motivated by these linguistic issues, the present article performs a critical discourse analysis of the National Strategic Plan and health brochures using the Discourse-Historical Approach (DHA). Strategies in the DHA were chosen to deconstruct how social actors are linguistically referred to and predicated, and how argumentation transpires in the texts. While heart disease is represented as a lethal NCD, diabetes is represented as an NCD and a risk factor for heart disease. The former is caused by hereditary factors and unhealthy lifestyles, but the latter is manageable yet uncurable. However, the two NCDs are depicted as a threat to the economy and country. Moreover, the government and citizens are contrasted. The government is given a positive evaluation because it helps to control the two NCDs while Malaysian NCD patients seem to burden the health services, and they need to endeavor to avoid NCDs. The contrast is exemplified by the topoi of threat and urgency to justify actions and decisions regarding health. The National Strategic Plan and various brochures convey a consistent ideology that the two NCDs should be prevented, and individual responsibility is required. This study sheds light on the underlying ideologies that shape the texts, particularly the portrayal of NCDs as an individual responsibility.